Contamination of Heavy Metals (Pb and Cu) at Tin Sea Mining Field and Its Impact to Marine Tourism and Fisheries - Sudirman Adibrata; Muh. Yusuf; Irvani Irvani; Maulana Firdaus (Marine Science Department Diponegoro University, 2021)
The dynamics of heavy metals (Pb and Cu) distribution near sea mining locations can show a negative impact on fisheries resource management. The study was conducted at the coastal area of Tanah Merah Beach, Central Bangka Regency, the geographical location at 02o12'50